(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The library has increased their resources continuously by receiving funds from various agencies and institutions. For the fulfilling of users’ needs and demands, there is a basic requirement for continuing the marketing of library resources and services. This paper has discussed the details of needs and importance of marketing in libraries, various marketable resources and services available in the library. It is talked about on the 7 Ps of marketing strategies in libraries like a product, price, place, promotion, participants, physical evidence and process. It also discussed the utilization of social media and e-marketing for library services. Marketing of library resources and services is necessity in the present ICT age. Library users are not aware of all the library resources and services available for their use. Library personnel have to provide various training/orientation programs to users for optimally utilization of library resources and service.